The Index Card Match Strategy to Improve Students’ Grammar Learning Outcomes at the Islamic Boarding School - Nurlaila, Riza; Anggara, Rinto; Nuruddin, Alfy Mamduh (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Purpose - This study aims to examine the effectiveness of the Index Card Match strategy in enhancing learning activities and nahwu learning outcomes among students of class 2D at Pondok Pesantren Darunnajah Jakarta. Design/Methodology/Approach - This research employed a Classroom Action Research (CAR) design based on the Kemmis and Taggart model, involving 27 students. The study was conducted in two cycles, each consisting of the stages of planning, action, observation, and reflection. Data were collected through interviews, classroom observations, achievement tests, and documentation. The data were analyzed using descriptive qualitative and quantitative approaches to provide a comprehensive understanding of the learning process and outcomes. Findings - The results reveal a significant improvement in students’ learning activities, which increased from 74.66% in Cycle I to 85.93% in Cycle II. In addition, students’ learning outcomes improved substantially, as the pass rate increased from 77.77% with an average score of 6.96 in Cycle I to 100% with an average score of 8.96 in Cycle II. These results indicate that the Index Card Match strategy effectively promotes student engagement and enhances achievement in nahwu learning. Research Limitations/Implications - This study was limited to one class and focused exclusively on nahwu instruction. However, the findings offer meaningful implications for Arabic language teachers in implementing active learning strategies. Future studies should involve larger samples and comparative designs to strengthen the generalizability of the findings and expand their contribution to Arabic language pedagogy.